Jak to dobrze, że pan przeżył... Aktorstwo filmowe Jana Świderskiego - GUZEK, MARIUSZ (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
It’s a good job you survived... Jan Świderski’s fi lm acting Jan Świderski was one of the most original figures of the Polish stage. As an actor, director, theatre director and teacher he left a considerable legacy. He also enjoyed appearing on television. However, he never warmed to the idea of film. His filmography from 1947-1988 totals a mere 14 films, including one leading role. Despite this modest output, these roles do create a kind of acting strategies, which supplement his stage output in the form of counterpoint. The text presents two variants of his screen characters - the old man and the scoundrel, who were rather unsuccessful attempts at transferring the tried-and-tested theatre formula to the demanding requirements of the film set.